Dental Students' Perception and Self-Perceived Confidence Level in Key Dental Procedures for General Practice and the Impact of Competency Implementation on Their Confidence Level, Part I (Prosthodontics and Conservative Dentistry) - Wijdan R. Elmanaseer; Salah A. Al-Omoush; Rasha A. Alamoush; Rawan Abu Zaghlan; Firas Alsoleihat (Hindawi Limited, 2023)
Background. Evaluating the level of dental students' competence is crucial for validating their preparedness for graduation. Confidence has a significant role in achieving competence. There are limited studies that assess the level of self-perceived confidence among final-year dental students regarding their ability to conduct key dental procedures. This study aims to assess the self-perceived confidence level of final-year dental students in performing essential dental procedures across various dental disciplines and to assess the effect of implementing competencies in the curriculum on the self-perceived confidence level of students by comparing two cohorts of final-year students in two different years 2016 (Traditional Cohort) and 2019 (Competencies Cohort). Materials and Methods. An questionnaire was answered by two cohorts of final-year dental students: one group in 2016 before the implementation of the competency-based assessment system (group 1, n = 153), and the other in 2019 after the implementation of this system (group 2, n = 199), the same questionnaire was used for both cohorts. The results from the two groups were compared regarding the degree of self-perceived confidence in conducting key dental procedures. The data were analysed using SPSS statistics and Levene's Test for Equality of Variances and t-test for Equality of Means calculated. Results. Group 1 showed a significantly higher means of self-perceived confidence levels than group 2 in the ability to conduct seven out of the 20 prosthodontics procedures studied: providing patients with Cobalt-Chromium (Co-Cr) removable partial dentures (RPD) (3.77 vs. 3.56), providing the patient with Acrylic RPD (3.70 vs. 3.23), treatment planning for partially edentulous patients (3.83 vs. 3.34), giving OHIs for denture patients (4.17 vs. 3.95), dealing with CD postinsertion complaints (3.97 vs. 3.76), giving postinsertion instructions for removable prostheses cases (4.12 vs. 3.82), and providing patients with immediate dentures (2.67 vs. 2.32). The same applies to 6 out of 16 conservative dentistry procedures: placing anterior composite (4.41 vs. 4.12), placing posterior composite (4.43 vs. 3.88), placing posterior amalgam (4.29 vs. 4.02), placing matrix band for Class II restorations (4.24 vs. 3.71), placing a prefabricated post (3.34 vs. 2.88), and placing fiber post (3.45 vs. 3.34). On the other hand, group 2 shows higher means of self-perceived confidence than group 1 in only two conservative dentistry procedures: onlay restorations (2.18 vs. 2.76) and inlay restorations (2.22 vs. 2.75). No significant differences in means of self-perceived confidence were found between the two groups in the remaining 21 procedures studied. Conclusions. This study has shown that final-year dental students have high self-perceived confidence levels in doing simple dental procedures yet less confidence in more complex ones. Although, students' self-perceived confidence decreases after the introduction of a competency-based assessment system. Competency implementation and execution criteria may differ between schools which may have an impact on final outcomes. Hence, there is a need for regular evaluation of competencies being assessed to maintain a curriculum that is up to date.